Novel effects of Rosa damascena extract on memory and neurogenesis in a rat model of Alzheimer's disease. Issue 4 (2nd January 2014) - Esfandiary, Ebrahim; Karimipour, Mohammad; Mardani, Mohammad; Alaei, Hojjatallah; Ghannadian, Mustafa; Kazemi, Mohammad; Mohammadnejad, Daryoush; Hosseini, Nasrin; Esmaeili, Abolghasem
<x xml:space="preserve">Abstract</x> The number of older people who are suffering from memory impairment is increasing among populations throughout the world. Alzheimer's disease (AD) affects about 5% of people over 65 years old. The hippocampus, a brain area critical for learning and memory, is especially vulnerable to damage in the early stages of AD. Emerging evidence suggests that loss of neurons and synapses are correlated with dementia in this devastating disease. Therefore, neurogenesis and synaptogenesis in adulthood could serve as a preventive as well as a therapeutic target for AD. This study investigated the effect of Rosa damascena extract on neurogenesis and synaptogenesis in an animal model of AD. Molecular, cellular, and behavioral experiments revealed that this treatment could induce neurogenesis and synaptic plasticity and improve memory in AD. Our study suggests that R. damascena is a promising treatment for mild memory impairments and AD. © 2013 Wiley Periodicals, Inc.